Calcium–axonemal microtubuli interactions underlie mechanism(s) of primary cilia morphological changes - Buljan, V.; Graeber, M.; Holsinger, R.; Brown, Daniel; Hambly, B.; Delikatny, E.; Vuletic, V.; Krebs, X.; Tomas, I.; Bohorquez-Florez, J.; Liu, G.; Banati, R. (SPRINGER, 2018)
We have used cell culture of astrocytes aligned within microchannels to investigate calcium effects on primary cilia morphology. In the absence of calcium and in the presence of flow of media (10 µL.s-1) the majority (90%) of primary cilia showed reversible bending with an average curvature of 2.1 ± 0.9 × 10-4 nm-1. When 1.0 mM calcium was present, 90% of cilia underwent bending. Forty percent of these cilia demonstrated strong irreversible bending, resulting in a final average curvature of 3.9 ± 1 × 10-4 nm-1, while 50% of cilia underwent bending similar to that observed during calcium-free flow. The average length of cilia was shifted toward shorter values (3.67 ± 0.34 µm) when exposed to excess calcium (1.0 mM), compared to media devoid of calcium (3.96 ± 0.26 µm). The number of primary cilia that became curved after calcium application was reduced when the cell culture was pre-incubated with 15 µM of the microtubule stabilizer, taxol, for 60 min prior to calcium application. Calcium caused single microtubules to curve at a concentration ˜1.0 mM in vitro, but at higher concentration (˜1.5 mM) multiple microtubule curving occurred. Additionally, calcium causes microtubule-associated protein-2 conformational changes and its dislocation from the microtubule wall at the location of microtubule curvature. A very small amount of calcium, that is 1.45 × 1011 times lower than the maximal capacity of TRPPs calcium channels, may cause gross morphological changes (curving) of primary cilia, while global cytosol calcium levels are expected to remain unchanged. These findings reflect the non-linear manner in which primary cilia may respond to calcium signaling, which in turn may influence the course of development of ciliopathies and cancer.